Selected Topical Agents Used in Traditional Chinese Medicine in the Treatment of Minor Injuries- A Review - Leung, Ping-chung; Ko, Erik Chun-hay; Siu, Wing-sum; Pang, Ellie Suet-yee; Lau, Clara Bik-san (Frontiers in Pharmacology, 2016)
Topical medicinal patches have been popular for the treatment of minor injuries like sprains and avulsions. Other inflammatory conditions like chronic musculo-tendinous pain and or fasciitis are also taken care of by local ointments or rubs. In the oriental communities, medicinal herbs frequently form the major components of the patches. In spite of the lack of scientific evidence of efficacy, the popularity of such traditional application persists for centuries. In this era of evidence-based clinical treatment, there is an urgent need to look into this traditional practice. The purpose should include a scientific verification of the efficacy of the practice, and once proven, further explorations would be indicated to bring the practice to a higher level. A system of comprehensive exploration was proposed and practiced in the past years to fulfill the aspiration. The research consisted of four areas: (1) Identification of the suitable medicinal herbs for the topical study; (2) Study of the biological activities of the selected herbs, concentrating on the areas of anti-inflammation, anti-oxidation, angiogenesis and cellular proliferation; (3) Study on the transcutaneous transport of the chemicals of the selected herbs to deeper tissues; and (4) Pilot clinical studies on common superficial inflammatory musculo-skeletal conditions to give objective clinical evidences to the topical applications. Five herbs were identified as suitable candidates of study. They were put into relevant laboratory platforms and were proven to be anti-oxidant, anti-inflammatory and pro-angiogenic. Three of the herbs were prepared as topical patches with an enhancer and used to treat three common ailments in pilot clinical trials, viz., plantar fasciitis, undisplaced metatarsal fracture and tendonitis of the wrist (de-Quervain’s disease) and the elbow (Tennis elbow). The clinical results of the pilot studies were very positive. It is therefore concluded that further explorations are justified to create medicinal herb patches of even greater efficacy.